2010
DOI: 10.1159/000276370
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cognitive Behavioural Therapy for the Treatment of Chronic Stress in Patients with Lupus Erythematosus: A Randomized Controlled Trial

Abstract: Background: Chronic stress worsens the quality of life (QOL) of lupus patients by affecting their physical and psychological status. The effectiveness of a cognitive-behavioural intervention in a group of patients with lupus and high levels of daily stress was investigated. Methods: Forty-five patients with lupus and high levels of daily stress were randomly assigned to a control group (CG) or a therapy group (TG); they received cognitive behavioural therapy (CBT) which consisted of ten consecutive weekly sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
1
18

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(108 citation statements)
references
References 72 publications
5
83
1
18
Order By: Relevance
“…However, there is a subset of patients (approximately 40%) that remain in discomfort and they can benefit from psychosocial interventions (Dobkin et al, 2001). None of the studies found significant immunological changes in the index of disease activity (Navarrete-Navarrete et al, 2010;Sohng, 2003).…”
Section: Pre-and Post-test (N=10)mentioning
confidence: 89%
See 1 more Smart Citation
“…However, there is a subset of patients (approximately 40%) that remain in discomfort and they can benefit from psychosocial interventions (Dobkin et al, 2001). None of the studies found significant immunological changes in the index of disease activity (Navarrete-Navarrete et al, 2010;Sohng, 2003).…”
Section: Pre-and Post-test (N=10)mentioning
confidence: 89%
“…The literature reviewed suggests that there is a benefit for patients receiving psychological treatment in coping adjunct with medical treatment, along with achieving effects such as reduction in anxiety and depression (Navarrete-Navarrete et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados encontrados mostraron por un lado que la terapia cognitivo-conductual de afrontamiento al estrés disminuyó las puntuaciones en las variables de estrés percibido, vulnerabilidad al estrés, preocupaciones, somatizaciones, sensibilidad interpersonal, depresión, ansiedad y ansiedad fóbica. Estos resultados confirman los hallazgos de otros estudios dirigidos a comprobar la eficacia de esta terapia para reducir los niveles de estrés y el malestar emocional (Navarrete-Navarrete et al, 2010;Peralta-Ramírez et al, 2009). Por otro lado, con respecto a las variables de personalidad también encontramos que tras la terapia se incrementan los niveles de optimismo, extraversión y conciencia/responsabilidad.…”
Section: Discussionunclassified
“…Numerosos estudios han mostrado que mediante terapias cognitivo-conductuales se consigue controlar el estrés, así como variables asociadas a éste: ansiedad (Hofmann y Smits, 2008; Navarrete-Navarrete et al Debido al fuerte impacto que este trastorno puede llegar a suponer en las personas, se han desarrollado programas en diferentes muestras de población tratando de paliar dichas consecuencias (Navarrete-Navarrete et al, 2010; PeraltaRamírez, et al, 2009;. En concreto, Butler, Chapman, Forman y Beck (2006) examinaron 16 meta-análisis de los efectos de la terapia cognitivo-conductual y encontraron mejoras en una gran variedad de problemas entre los que destacaban depresión mayor, trastorno de ansiedad generalizada y trastorno de estrés post-traumático.…”
Section: Introductionunclassified
See 1 more Smart Citation